Thriving beyond the stethoscope: Unveiling positive mental health among medical students at a University in South Africa - Rajesh Vagiri; Mabitsela Mphasha; Varsha Bangalee; Wandisile Grootboom; Letlhogonolo Makhele; Neelaveni Padayachee (Dialogues in Health)
Introduction: Medical education presents significant challenges for medical students' mental health. Medical students are a vulnerable group, experiencing higher rates of mental health disorders, which can have implications for their well-being and academic performance. Consequently, evaluating Positive mental health (PMH) has become significant in a contemporary and demanding society, particularly among university students. Aim: This study aimed to assess the levels of PMH and identify the association between PMH domains and socio-demographic and health related variables among medical students enrolled at a university in South Africa. Methods: This quantitative, descriptive, and cross-sectional survey was conducted with 144 undergraduate medical students. Data were collected using a multi-dimensional PMH instrument and a sociodemographic and health related questionnaire, from 144 undergraduate medical students. The university's Research and Ethics Committee granted ethical clearance for the study. Results: The data were analysed using IBM SPSS version 29. The majority of the students were older than 20 years (79.2 %, n = 114), had no prior history of psychiatric illness, and had not previously taken any psychiatric medication (94.4 %, n = 136). More than half of the participants were single (66 %, n = 95), identified as Christians (76.4 %, n = 110), received a bursary (78.5 %, n = 113), had families living in rural areas (71.5 %, n = 103) and resided in the university housing (73.6 %, n = 106). Gender (p = 0.01), age (p = 0.02), religious affiliation (p = 0.03), history of psychiatric illness (p = 0.05) and treatment for psychiatric illness (p = 0.05) had a significant influence on the Total PMH score. Male participants reported higher mean scores in most PMH domains, excluding emotional support and spirituality domains. Participants aged between 22 and 23 years reported lower mean scores in Total PMH and most PMH domains. There is a significant difference in mean scores with gender (p = 0.02) and religious affiliation (p = 0.00) in the spirituality domain. Conclusion: The study results emphasised the complex nature of mental health and provided a rationale for assessing the various aspects of PMH in university students. By implementing evidence-based strategies and providing adequate support, medical schools can better support the mental health and well-being of their students, ultimately cultivating a healthier and more resilient future healthcare workforce.